2013
DOI: 10.1136/bmjopen-2012-001167
|View full text |Cite
|
Sign up to set email alerts
|

The use of glucosamine for chronic low back pain: a systematic review of randomised control trials

Abstract: ObjectivesTo ascertain whether the use of oral glucosamine influences symptoms or functional outcomes in patients with chronic low back pain (LBP) thought to be related to spinal osteoarthritis (OA).DesignSystematic review of randomised control trials. Searches were performed up to March 2011 on Medline, AMED, CINHAL, Cochrane and EMBASE with subsequent reference screening of retrieved studies. In addition, the grey literature was searched via opensigle. Included studies were required to incorporate at least o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
0
6
0
4
Order By: Relevance
“…The evidence review identified one SR with very low quality of evidence that included three trials. 36 Two of the included studies showed no difference between glucosamine and placebo. The benefits and harms/burden are balanced.…”
Section: Glucosaminementioning
confidence: 97%
“…The evidence review identified one SR with very low quality of evidence that included three trials. 36 Two of the included studies showed no difference between glucosamine and placebo. The benefits and harms/burden are balanced.…”
Section: Glucosaminementioning
confidence: 97%
“…The overall quality of evidence was evaluated according to the Grades of Recommendation, Assessment, Development, and Evaluation (GRADE) criteria, as in previous research 18 ( Table 2 ). In brief, studies that were observational, limited, inconsistent, indirect, or imprecise or exhibited publication bias were considered to yield “low-quality” evidence.…”
Section: Methodsmentioning
confidence: 99%
“…С другой стороны, имеется лишь несколько хорошо организованных исследований, в которых изучался терапевтический потенциал СПМД при ХНБС. Метаанализ 3 РКИ (n=309) продолжительностью от 12 нед не показал достоверных различий между глюкозамином и плацебо по снижению боли и улучшению функции у пациентов с ХНБС [71]. Весьма показательны данные Р. Wilkens и соавт.…”
Section: Cимптоматические препараты медленного действияunclassified